Transforming Motivation into Achievement: The Role of Self-Efficacy Among Senior High School Students in Eastern Indonesia - Dinda Eka Wulandary (Proceedings of International Conference of Graduate School on Sustainability, 2026)
This study aims to examine the mediating role of self-efficacy in the relationship between academic anxiety, learning motivation, and student learning outcomes at SMA Negeri 2 Halmahera Timur. Understanding how these psychological factors interact is crucial, particularly in the context of schools in Eastern Indonesia. This research employed a quantitative explanatory approach, using a random sample of 228 students. Data were collected using questionnaires and analyzed using the Process Hayes macro within SPSS to test the mediation model. The instruments demonstrated strong validity (r > 0.355) and reliability (Alpha > 0.665). The results indicate that self-efficacy positively and significantly affects learning outcomes, confirming its role as a key psychological determinant of academic success. Crucially, the study found that self-efficacy acts as a full mediator between learning motivation and learning outcomes. This means that motivation alone is insufficient; its positive effect on achievement is primarily realized only when students possess high self-efficacy. Conversely, academic anxiety was found to have no significant direct or indirect effect on learning outcomes, suggesting that for this specific student population, anxiety is not a dominant factor impairing performance, either directly or through self-efficacy. These findings emphasize the need to focus on self-efficacy enhancement programs in educational settings.